Effectiveness of Multimodel Electronic Teaching Materials on Mechanical Waves to Enhance Problem-Solving Skills - Ramadayanti, Sri; Salam M, Abdul; Dewantara, Dewi (Program Studi Pendidikan Fisika, 2025)
This multimodel-based electronic teaching material is one of the innovations in supporting learning development to train problem-solving skills. The purpose of this study is to provide effective multimodel-based electronic teaching materials for use in learning. The ADDIE model is used in the research design which is a project of research and development. A total of 22 students of class XI MIPA 2 became the test subjects of this study. Data were obtained from the results of students' cognitive learning. Quantitative descriptive analysis was used for data analysis. The electronic teaching materials obtained were: (1) classified as effective, because the N-gain THB was in the high category; and (2) stated that it can be an alternative in training students' problem-solving skills, because the N-gain of problem-solving skills was in the medium category. In conclusion, the multimodel-based electronic teaching materials that were created are effective in physics learning to train students' problem-solving skills.